A comparative and experimental study on gradient and genetic optimization algorithms for parameter identification of linear MIMO models of a drilling vessel - Bańka, Stanisław (1944-2014); Brasel, Michał; Dworak, Paweł; Jaroszewski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents algorithms for parameter identification of linear vessel models being in force for the current operating point of a ship. Advantages and disadvantages of gradient and genetic algorithms in identifying the model parameters are discussed. The study is supported by presentation of identification results for a nonlinear model of a drilling vessel.
Keywords: MIMO dynamic plant; identification; nonlinear systems